LOSS MODELING OF A PERMANENT MAGNET DC MOTOR DRIVE WATER PUMPING SYSTEM - Lujara, Nelson K (Tanzania Journal of Engineering and Technology, 2017)
The paper presents an analytical approach to the determination of losses in each of the sub-systems of the Photovoltaic (PV) Permanent Magnet DC Motor (PMDC) drive water pumping system with and without maximum power tracking. The losses of the system at varying heads are firstly, determined using parameters from the data sheets and then validated by experimental results. The results are used to establish the head and the flow rate optimal operating point of the system.